Wild Music : Sound and Sovereignty in Ukraine - Sonevytsky, Maria (Book collections on Project MUSE., 2019)
"Wild Music explores popular music in Ukraine, and specifically the interplay of musical exoticism with the politics of post-Soviet sovereignty. About the author: Maria Sonevytsky is an Assistant Professor of Music (Ethnomusicology) at the University of California, Berkeley. She performs with several bands including The Debutante Hour, Anti-Social Music, and Zozulka and produced an album called "The Chornobyl Songs Project" on Smithsonian Folkways in 2015 with Ensemble Hilka. She has also taught Ukrainian village songs, piano accordion, and assorted other things"--